Hand Transplants, Daily Functioning, and the Human Capacity for Limb Regeneration - Fitzpatrick, Susan M.; Brogan, David; Grover, Prateek (Frontiers in Cell and Developmental Biology, 2022)
Unlike some of our invertebrate and vertebrate cousins with the capacity to regenerate limbs after traumatic loss, humans do not have the ability to regrow arms or legs lost to injury or disease. For the millions of people worldwide who have lost a limb after birth, the primary route to regaining function and minimizing future complications is via rehabilitation, prosthetic devices, assistive aids, health system robustness, and social safety net structures. The majority of limbs lost are lower limbs (legs), with diabetes and vascular disorders being significant causal contributors. Upper limbs (arms) are lost primarily because of trauma; digits and hands are the most common levels of loss. Even if much of the arm remains intact, upper limb amputation significantly impacts function, largely due to the loss of the hand. Human hands are marvels of evolution and permit a dexterity that enables a wide variety of function not readily replaced by devices. It is not surprising, therefore, for some individuals, dissatisfaction with available prosthetic options coupled with remarkable advances in hand surgery techniques is resulting in patients undertaking the rigors of a hand transplantation. While not “regeneration” in the sense of the enviable ability with which Axolotls can replace a lost limb, hand transplants do require significant regeneration of tissues and nerves. Regaining sophisticated hand functions also depends on “reconnecting” the donated hand with the areas of the human brain responsible for the sensory and motor processing required for complex actions. Human hand transplants are not without controversy and raise interesting challenges regarding the human regenerative capacity and the status of transplants for enabling function. More investigation is needed to address medical and ethical questions prior to expansion of hand transplants to a wider patient population.